The Strategic Role Of Zakat And Waqf In Sustainable Poverty Alleviation: A Literature Review From The Perspective Of Islamic Economics - Zulkipli, Zulkipli; Basit, Abdul; Wajdi, Farid (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
Poverty in Indonesia remains a structural challenge that requires alternative approaches beyond conventional policies. Zakat and waqf, as instruments of Islamic social finance, possess great potential but remain underutilized due to institutional fragmentation and lack of policy integration. This study aims to construct a strategic integration model of zakat and waqf for poverty alleviation based on maqashid shariah principles. Using a qualitative approach through systematic literature review and thematic analysis, this research develops the Zakat-Waqf Based Development Framework (ZWDF), which emphasizes the integration of spiritual, institutional, and policy dimensions. The main contribution of this study lies in unifying normative and practical aspects to mainstream zakat and waqf as pillars of inclusive development. It recommends strengthening regulatory coherence and cross-institutional synergy to enable zakat and waqf to function as sustainable social policy instruments.